Implementasi Webgis Sebaran Lokasi Puskemas - Muhammad Wahyu Tambunan; Ibnu Rasyid Munthe (Jurnal Sistem Informasi, Teknik Informatika dan Teknologi Pendidikan, 2021)
The community has difficulty in finding detailed information on the location of the nearest health center health service. And this study aims to develop a mapping application as a means of a public health center that uses a geographic information system so that the location of the health center in Labuhan Batu district can be seen well. after this research was realized, among others, was to facilitate the people of Labuhan Batu district in accessing information and the location of the health center in Labuhan Batu district by using android In this study, researchers used the SDLC (system development life cycle) design method as a Webgis community health center design and used UML (unified modeling language) modeling as a geographic information system design model that can help and simplify problems that can meet modeling needs. This system can also display information about health center facilities so that it can make it easier for the community to find information on the health center facilities to be addressed.